Association between endometrial blood and clinical outcome in frozen single blastocyst transfer cycles - Zhang, Qian; Wang, Xiaolong; Li, Zhishu; Wang, Yinghua; Lu, Hai’Ou; Xiao, Yuhong; Yu, Yuexin (Frontiers in Physiology, 2023)
Background: The success of embryo transfer cycle depends mainly on the quality of embryo and endometrial receptivity. Ultrasound examination is still the most widely used non-invasive evaluation method for its advantages of convenience, non-invasiveness and repeatability. Ultrasound-measured endometrial blood flow is one of the important evaluation indicators of morphology. Aims: To investigate the effect of the number of endometrial blood flow branches on pregnancy outcome of frozen-thawed embryo transfer cycles which have undergoing hormone replacement therapy (HRT-FET). Material and methods: A retrospective cohort study was performed looking at a total of 1390 HRT-FET cycles from our reproductive medicine center between January 2017 to December 2021, which transferred one blastocyst frozen on day 5 with good quality in morphology. Associations between endometrial blood flow branches and pregnancy outcomes were evaluated with multivariable linear regression analysis. Results: The number of endometrial blood flow branches was independently associated with clinical pregnancy (OR 1.10; 95% CI 1.02-1.20). After adjusting for potential confounders, the effect size （odds ratio）was 1.09 (95% CI 1.00-1.19), and the results showed that the clinical pregnancy rate and live birth rate of T2 and T3 groups were significantly higher than those in group T1 (P < 0.05). Subgroup analysis showed that a consistent association between the endometrial blood flow branches and clinical pregnancy in all subgroups. Conclusions: Our study provided evidence for the influence of endometrial blood flow on pregnancy outcomes. There may be an independent association between the number of endometrial blood flow branches and pregnancy outcomes in frozen-thawed single blastocyst transfer cycles.